RUANG ASING DAN IDENTITAS ANNE FRANK DALAM NOVEL OTOBIOGRAFI DAS TAGEBUCH DER ANNE FRANK - Faizah, Nahla; Liyanti, Lisda (Universitas Hasanuddin, 2019)
Ethnic persecution often happens in several countries in the world. This has also been a part of german history in the second world war era which is renowned with the holocaust era during the Nazi regime. This article discusses one of the most famous autobiography in the world written by a jewish girl, named Anneliese Marie Frank. She is one of the victims of Nazi persecution. She wrote a diary entitled “The Diary of Anne Frank.” I am interested in researching the otherness concept of Anne’s hiding room and its effect on the development of Anne’s identity as a teenager. I use the qualitative research method focusing on the content analysis. The theories applied in this article are Alterity and identity, identity development of a teenager and also space theory (Ort und Nicht-Orte) theory by Marc Augé to analyze how Anne Frank interacted with several foreign matters she met in her hiding room and how the otherness within her space affects her identity development as a teenager. The results showed that Annex room was included in the category between “Orte” and “Nicht-Ort” which made Anne struggle with the existing alienation and could not reach her identity as a teenager well.